Cooling for sustainable development - Khosla, R; Miranda, N; Renaldi, R; Antonella, M; Philipp, T; Malcolm, M; Rafael, P; Anant, J; Francois, C; Caitlin, M (Nature Research, 2020)
The unprecedented rise in cooling demand globally is a critical blind spot in sustainability debates. We examine cooling as a system comprised of active and passive measures, with key social and technical components, and explain its link to all 17 Sustainable Development Goals. We propose an analytical and solution-oriented framework to identify and shape interventions towards sustainable cooling. The framework comprehends demand drivers; cradle-to-cradle stages; and system change levers. By intersecting cooling stages and levers, we discuss four specific, exemplary interventions to deliver sustainable cooling. We propose an agenda for research and practice to transition towards sustainable cooling for all.